The Influence of the Fundamental Parameters on the Mechanical Behavior of Coarse-Grained Soils - Ghizlane Ardouz; Khadija Baba; Latifa El Bouanani; Fatima Ezzahraa Latifi; Asmaa Dardouch (Salehan Institute of Higher Education, 2022)
Coarse-grained soils are a type of soil frequently found in civil engineering projects. The mechanical characterization of these soils is very difficult because of the presence of large-sized elements that disturb or prevent the realization of the tests. However, there is still no rational procedure to characterize coarse soils and determine their mechanical characteristics (cohesion and friction angle) for the calculation of slope stability or structures. The objectives of the research work are to contribute to the improvement of the knowledge of the mechanical behavior of matrix coarse-grained soils and to propose a rational procedure to characterize them. In order to achieve these objectives, it is important to understand the influence of the fundamental parameters related to the mode of reconstitution on the mechanical behavior of the coarse soils: volume fraction, particle size distribution and spread, consolidation level, and the initial state of the matrix. Tests are carried out using the large-sized triaxial testing device in drained conditions. With natural coarse-grained soils, it is very difficult to conduct repeatability tests to validate the results. For this reason, we will study a particular category of coarse-grained soils composed of inclusions (coarse elements) within a fine sandy matrix (matrix coarse-grained soils), using a reference soil composed of a mix of sand and gravel. The results show that for both states of sand compaction (ID=0.4 and ID = 0.8), the shear strength of the soil increases with the increase in the proportion of gravel. This increase is more marked in the case of uniform 8/10 mm gravel. Thus, the size of inclusions has no significant influence on the value of qmax. Doi: 10.28991/CEJ-2022-08-08-012 Full Text: PDF